Portrait of the visual arts : meeting the challenges of a new era - McCarthy, Kevin F., 1945-; Ondaatje, Elizabeth Heneghan; Brooks, Arthur C., 1964-; Szanto, Andras; RAND Education (Institute); Rand Corporation; Pew Charitable Trusts (Santa Monica, CA : RAND, 2005)
The third in a series that examines the state of the arts in America, this analysis shows, in addition to lines around the block for special exhibits, well-paid superstar artists, flourishing university visual arts programs, and a global expansion of collectors, developments in the visual arts also tell a story of rapid, even seismic change, systemic imbalances, and dislocation. Using the performing arts as a comparison, this book shows that the visual arts appear better suited to the changing consumption and life styles of American consumers. Their visual character, for example, makes them easily and readily experienced. They require less time commitment than other art forms and their appreciation can be tailored to Americansb2 (Bpatterns of leisure consumption. But is the current picture as rosy as rising attendance figures and art price indices suggest? And will this success continue into the future? Using a systemwide approach to examine the visual arts in the context of the broader arts environment and to identify the major challenges they face, this book examines the possible answers to these questions. Earlier books in the series include The Performing Arts in a New Era (MR-1367-PCT, 2001) and From Celluloid to Cyberspace: The Media Arts and the Changing Arts World (MR-1552-RF, 2002).s
"RAND Research in the Arts."
Includes bibliographical references (p. 117-128).
Also available on the internet via WWW in PDF format.
Keywords: Art -- Economic aspects -- United States; Art -- Forecasting; Art -- United States -- Marketing